Labor Productivity and the Elasticity of Factor Substitution in West German Industries 1950-1960 - Roskamp, Karl W. (The Review of Economics and Statistics, 1977)
Abramovitz, M., and P. A. David, Reinterpreting Economic Growth: Parables and Realities, American Economic Review 63 (May 1973), 428439. Arrow, K., H. B. Chenery, B. Minhas, and R. M. Solow, Capital-Labor Substitution and Economic Efficiency, this REVIEW 43 (Aug. 1961), 225-250. Baer, W., and M. E. A. Herve, Employment and Industrialization in Developing Countries, Quarterly Journal of Economics 80 (Feb. 1966), 88-107. Behrman, J. R., Sectoral of Substitution between Capital and Labor in a Developing Economy: Time Series Analysis in the Case of Postwar Chile, Econometrica 40 (Mar. 1972), 311-326. Dhrymes, P. J., and P. Zarembka, Elasticities of Substitution for Two-Digit Manufacturing Industries: A Correction, this REVIEW 52 (Feb. 1970), 115-117. Diamond, P. A., and D. McFadden, Identification of the Elasticity of Substitution and the of Technical Change: An Impossibility Theorem, Working Paper No. 62, University of California (Berkeley), 1965. Fuchs, V., Capital-Labor Substitution: A Note, this REVIEW 45 (Nov. 1963), 436-438. Gupta, S. B., Some Tests of the International Comparisons of Factor Efficiency with the CES Production Function, this REVIEW 50 (Nov. 1968), 470-476; Reply by Archen Minsol (ACMS), 477-479. Kelley, A. C., J. G. Williamson, and R. J. Cheetham, Dualistic Economic Development (Chicago: University of Chicago Press, 1972). Lucas, R. E., Jr., Labor-Capital Substitution in U.S. Manufacturing, in A. C. Harberger and M. J. Bailey (eds.), Taxation of Income and Capital (Washington, D.C.: Brookings Institution, 1969), 223-274. Moroney, J. R., Identification and Specification Analysis of Alternative Equations for Estimating the Elasticity of Substitution, Southern Economic Journal 37 (Jan. 1970), 287-299. Nerlove, M., Recent Empirical Studies of the CES and Related Production Functions, in M. Brown (ed.), Theory and Empirical Analysis of Production (New York: Columbia University Press, 1967), 55-122. Ranis, G., Sector Labor Absorption, Economic Development and Cultural Change 21 (Apr. 1973), 387-408. Sato, K., Production Functions and Aggregation (Amsterdam: North-Holland Publishing Company, 1975). Schydlowsky, D. M., and M. Syrquin, The Estimation of CES Production Functions and Neutral Efficiency Levels Using Effective Rates of Protection as Price Deflators, this REVIEW 54 (Feb. 1972), 78-83. Sveikauskas, L., Bias in Cross-Section Estimates of the Elasticity of Substitution, International Economic Review 15 (June 1974), 522-528. , The Productivity of Cities, Quarterly Journal of Economics 89 (Aug. 1975), 393-413. United Nations, Textile Industry in Latin America (New York, 1963). United Nations Industrial Development Organization, Textile Industry (New York, 1969). Zarembka, P., On the Empirical Relevance of the CES Production Function, this REVIEW 52 (Feb. 1970), 47-53.